2018
DOI: 10.3389/fgene.2018.00468
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk for Psychiatric Disorders and Telomere Length

Abstract: Background: Previous studies have revealed associations between psychiatric disorder diagnosis and shorter telomere length. Here, we attempt to discern whether genetic risk for psychiatric disorders, or use of pharmacological treatments (i.e., antidepressants), predict shorter telomere length and risk for aging-related disease in a United Kingdom population sample.Methods: DNA samples from blood were available from 351 participants who were recruited as part of the South East London Community Health (SELCoH) S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…We aimed to assess how HIV-1 acquisition risk might be moderated by an individual's immune profile prior to infection, and so we tested how polygenic risk for HIV-1 acquisition correlated with the expression of 35 inflammatory markers. We studied HIV-1-negative population controls from the South East London Community Health Study (SELCoH) [45][46][47] , where HIV-1-negative status was determined based on self-report. For further details on the full SELCoH study, please see Hatch et al 43 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to assess how HIV-1 acquisition risk might be moderated by an individual's immune profile prior to infection, and so we tested how polygenic risk for HIV-1 acquisition correlated with the expression of 35 inflammatory markers. We studied HIV-1-negative population controls from the South East London Community Health Study (SELCoH) [45][46][47] , where HIV-1-negative status was determined based on self-report. For further details on the full SELCoH study, please see Hatch et al 43 .…”
Section: Methodsmentioning
confidence: 99%
“…The first phase aimed to assess common physical and mental disorders in South East London; the second, to examine the roles of historical social context and policy in shaping patterns of health inequalities; and the third, to collect biological specimens from a subset of participants, including blood for serum separation and DNA for genotyping. Serum and DNA were extracted and stored at −80 °C until use, as described previously 47,48 .…”
Section: Methodsmentioning
confidence: 99%
“…The incidences of mental health problems such as depression, and obsessive compulsive-, panic-, and anxiety disorder continue to increase year after year for a variety of reasons (1). Previous research has shown that personal factors such as age, sex, alcohol consumption, smoking and social factors (e.g., low socioeconomic status) contribute to the development or triggering of mental health problems (2,3). Data from adult populations has shown that high-quality diets are associated with better mental health outcomes (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Relative telomere length was quantified using DNA samples and a modified version of the quantitative Polymerase Chain Reaction (qPCR) protocol described by Cawthon and colleagues (52), as used by our lab previously (7,14,29,53). First, the protocol assayed the telomere variable repeat region (TTAGGG), and the cycle threshold (Ct) required to reach a predetermined level of fluorescence: this correlated with the number of telomere repeats present in the individual samples.…”
Section: Telomere Length Measurementsmentioning
confidence: 99%
“…This statistic primarily reflects the higher prevalence of comorbid age-related diseases, including coronary artery disease, diabetes and dementia, which contribute to early mortality (3,4). Epidemiological findings such as these, have prompted researchers to consider whether faster ageing represents a core component to the pathophysiology of psychiatric disorders, or whether it represents the consequences of unhealthy lifestyles and stressful experiences, more common amongst those diagnosed with a psychiatric disorder (5,6).…”
Section: Introductionmentioning
confidence: 99%